Makna Dharmagita dan Implikasinya Terhadap Hipertensi Di Sekaa San- thi Giri Merta Banjar Kembang Merta, Candikuning, Baturiti, Tabanan - Diantari, Ida Ayu Putu Mirah (Indonesian Academia Health Sciences Journal, 2020)
Objective: Hypertension is a common disease in the community, it is necessary to handle or prevent it, therefore, the incidence of hypertension can decrease, one of the cultures in Bali is able to reduce hypertension, namely dharmagita. Dharmagita is a spiritual song that contains truth and justice used in the implementation of Hindu religious ceremonies. This study aimed to determine the dharmagita and hyperten- sion in Sekaa Shanti Giri Merta. Methods: used in this study was qualitative paradigmatic interpretive with case study design. The informants interviewedwere six informants, including one key in- formant (the chairman of sekaa shanti). All informants are members of Sekaa Shanti GiriMerta. Results: This study showed that the informants who implemented dharmagita viewed from the implications of doing dharmagita had controlled blood pressure, name- ly systolic blood pressure 110-120mmHg and diatolic blood pressure between 70- 80mmHg. The results of this study can be used as scientific information to under- stand the implementation of dharmagita against hypertension Conclusion: The results of this study can be used as scientific information to under- stand the implementation of dharmagita against hypertension.